2001
DOI: 10.1021/ma011304o
|View full text |Cite
|
Sign up to set email alerts
|

Substituted Cyclopropenium Salts as Photoinitiators for Cationic Polymerization of Glycidyl Phenyl Ether

Abstract: A new series of triarylcyclopropenium tetrakis(pentafluorophenyl)gallates (I) were synthesized by anion exchange. These salts are photoacid generators from which we have measured the rates of acid release using the indicator Quinaldine Red (QR). Electron-donating substituents on the aromatic ring slow the rate of photoacid release. Cationic photopolymerization of glycidyl phenyl ether (GPE) was also examined. With 1 wt % triphenylcyclopropenium (TPCP) gallate, 90% of conversion of GPE was achieved within 20 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…Fluorinated copolymer network formation was followed by ATR spectroscopy with the characteristic absorption band of epoxide group at 910 cm -1 . Epoxide conversion depends on the nature and proportion of photo-initiator, irradiation time, source power, temperature and epoxide concentration [24][25][26][27]. Figure D80T20, D50T50 and D20T80 ones versus time for a film thickness of 25 µm.…”
Section: Gas Permeabilitymentioning
confidence: 99%
“…Fluorinated copolymer network formation was followed by ATR spectroscopy with the characteristic absorption band of epoxide group at 910 cm -1 . Epoxide conversion depends on the nature and proportion of photo-initiator, irradiation time, source power, temperature and epoxide concentration [24][25][26][27]. Figure D80T20, D50T50 and D20T80 ones versus time for a film thickness of 25 µm.…”
Section: Gas Permeabilitymentioning
confidence: 99%
“…When combined with a co-initiator such as a carbonyl compound or alcohol, they are effective initiators for thermal epoxy curing [15]. It has been demonstrated that (TPCP) is an effective cation for thermal initiation of cationic polymerization of glycidyl phenyl ether, when paired with Ga(C6F5)4 - [16]. [TPCP] [Ga(C6F5)4] requires cyclohexanone to form the actual initiating species [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that (TPCP) is an effective cation for thermal initiation of cationic polymerization of glycidyl phenyl ether, when paired with Ga(C6F5)4 - [16]. [TPCP] [Ga(C6F5)4] requires cyclohexanone to form the actual initiating species [16]. In the presence of trace amounts of water, [TPCP] [Ga(C6F5)4] also acts as a photoinitiator in polymerization of glycidyl phenyl ether [17].…”
Section: Introductionmentioning
confidence: 99%
“…Control of polymerization and the curing initiation process have been widely investigated in the fields of polymer science and technology, and especially external stimulation-induced polymerizations are of quite interest due to control of the initiation step of polymerization. For the past decades, numerous numbers of new latent initiators, which show no activity under normal polymerization conditions but release active species by external stimulation such as heating or photoirradiation, have been widely developed since latent initiators are useful in several industrial fields such as paints, inks, epoxy molding compounds, and photoresists. Development of an efficient latent initiator has been desirable for enhancement of both storage stability and handling, and Pappas et al, Crivello et al, Abu-Abdoun et al, Yagci et al, Toba et al, Li et al , and Endo et al have developed various onium salt - based cationic thermal and/or photolatent initiators, e.g., benzylsulfonium, benzylpyridinium, and benzylammonium salts with less nucleophilic counteranions like hexafluoroantimonate and hexafluorophosphonate for the polymerization of styrene and epoxides. In addition, the rate of polymerizations initiated by onium salts increases with decreasing nucleophilicity of their counteranion, e.g., BF 4 < PF 6 < AsF 6 < SbF 6 < B(C 6 F 5 ) 4 .…”
mentioning
confidence: 99%